Optimasi Aplikasi Asap Cair Menggunakan Maltodekstrin Melalui Sistem Nanoenkapsulasi Terhadap Pengawetan Siomay - Iswantoro, Andy; Mufidah, Nur; Dungga, Maria Ernesta ; Abrina Anggraini , Sinar Perbawani (Fakultas Teknik Universitas Tribhuwana Tunggadewi, 2019)
Siomay is a product made from fish made by steaming. However, dumpling have a relatively short shelf life at room temperature. This is because siomay has a high water content and water activity (aw). The need for natural preservatives is safe to consume to increase the shelf life of the dumplings. The technology used is liquid smoke. Volatile compounds in liquid smoke that play a role in bioreservative activity can evaporate during storage. So that technology development is needed to protect the active component by turning it into liquid smoke flour. Liquid smoke flour also has a higher phenol component compared to liquid smoke. The purpose of this study was to determine the optimal maltodextrin concentration and storage time in making nano-particles on siomay quality. The results of this study indicate that the content of liquid smoke is eliminated maltodectrin has titrated total acid from liquid smoke flour concentrated at 20%, 30%, 40% and liquid smoke is 1.024%; 0.832%; 0.896%; 2.495%. Water content of liquid smoke flour concentration of 20%, 30% and 40% is 9.436%; 7.186%; 8,333%.The optimum acidity level of siomay for maltodectrin concentration is 20%, 30%, 40% is 0.820%; 0.882%; 1.013% and optimum protein content in siomay from maltodectrin concentration of 20%, 30%, 40% is 3.95%; 3.98%;4.20%